MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN MEDIA POWER POINT KELAS III SDN 101964 JAHARUN A GALANG - Syaiful; Zon Saroha Ritonga (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2019)
This research aims to find out about the low learning scores of class III students at SD Negeri 101964 Jaharun A Galang which is known from the results of observations. The lack of innovation in learning makes some students look bored. Teachers usually use conventional methods, namely lectures, discussions, questions and answers, and assignments so that student activity in learning tends to be low. The approach used to overcome the problem in this research is by using Power Point learning media. Power Point media is a presentation tool, usually used to explain something that is summarized and packaged in a Power Point slide. So that readers can more easily understand our explanation through visualizations summarized in the slides. With Power Point media, it is hoped that all the material presented by the teacher will be accepted by students. Powerpoint media has the advantage/advantage of Power Point, namely that one of the features is that it provides the ability to create presentations that include music that plays the entire presentation or sound effects for certain slides. The method used is Classroom Action Research through two cycles consisting of planning, implementation, observation and reflection activities. The results of the research and discussion show that the results of the pre-test in the Pracycle obtained data from 40 students, 7 of whom were declared complete or 17.50% and 33 of them were incomplete, 82.50% with an average score of 47.75. The test results in Cycle I were obtained data from 40 students, 29 of them were declared complete or 82.50% and 11 students had not completed 27.50% with an average score of 72.75. The test results in Cycle II obtained data from 40 students, 36 of whom were declared complete or 90.00% and 4 people did not complete 10.00% with an average score of 83.50. For this reason, the researcher decided to complete the research in cycle II.